Inadequacies of Monetarism for Developing Countries with Mass Unemployment: A Recent Study - Chiselebwe Ng’andwe (Current Topics on Business, Economics and Finance Vol. 1, 2023)
This chapter offers a theoretical framework for examining the impact of expansionary monetary policy on inflation, output, and employment in developing economies. Monetarism’s relevance to developing economies is called into question. The shortcomings of monetarism for developing countries stem from the inapplicability of two critical monetarist assumptions to underdeveloped economies. The first is the existence of a natural rate of unemployment, also known as practical full employment. The second is that the impact of expansionary monetary policy is limited to aggregate demand (AD), with no effect on aggregate supply (AS). Inspired by Keynes (1936), the realistic analytical model for developing countries is developed based on realistic assumptions and objective conditions notably a) mass unemployment, and b) expansionary monetary policy shifts both the AD and AS curves. Keynes primary contribution was to highlight the role of Government intervention in stimulating and sustaining economic performance, and to provide a link between money supply and the real sector. In this model, expansionary monetary policy causes shifts to the right in AD and AS, resulting in a new stable equilibrium with unambiguously higher levels of output. However, the price level change will be determined by the elasticities of AD and AS (with respect to money supply changes). Because the elasticities of AD and AS are the ultimate determinants of the final impact of monetary policy on output and inflation, policy should concentrate on factors that affect the elasticities. These are the monetary policy efficiency drivers that can be pursued in order to achieve a high impact on output and employment while maintaining low inflation. Although this approach offers a genuine possibility for expansionary monetary policy to boost output while maintaining low inflation, the practical use is predicated on favourable conditions, which should include the economy’s ability to absorb increases in the money supply. An efficient system of financial intermediation that can direct more financial resources to the productive sector is essential. Before implementing an expansionary monetary policy to combat unemployment in underdeveloped economies with dysfunctional financial systems, it may be required to address the issue of financial intermediation.